2016
DOI: 10.1002/ijc.30519
|View full text |Cite
|
Sign up to set email alerts
|

Past sexual behaviors and risks of oropharyngeal squamous cell carcinoma: a case–case comparison

Abstract: The incidence of oropharyngeal squamous cell carcinomas (SCCs) is increasing and is believed to reflect changing sexual practices in recent decades. For this case-case comparative study, we collected medical and life-style information and data on sexual behavior from 478 patients treated at the head and neck clinic of a tertiary hospital in Brisbane, Australia. Patients were grouped as (i) oropharyngeal SCC (n = 96), (ii) oral cavity, larynx and hypopharynx SCC ("other HNSCCs," n = 96), (iii) other SCCs (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
(30 reference statements)
1
21
0
1
Order By: Relevance
“…A history of performing oral sex is a known risk factor for oropharyngeal cancer. 37 Previous evidence indicates that there is a higher probability of HPV transmission via vaginal oral sex compared with penile oral sex, 38 , 39 which would result in a higher burden of oral HPV infection among lesbian and bisexual women.…”
Section: Discussionmentioning
confidence: 99%
“…A history of performing oral sex is a known risk factor for oropharyngeal cancer. 37 Previous evidence indicates that there is a higher probability of HPV transmission via vaginal oral sex compared with penile oral sex, 38 , 39 which would result in a higher burden of oral HPV infection among lesbian and bisexual women.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the main HPV genotype identified in oral rinse samples from the general Scottish population was HPV 16 [11]. HPV is thought to be acquired through sexual exposure [12,13] although the natural history of HPV-associated OPC is not as well defined as other HPVassociated neoplasms such as cervix. Although the increase in OPC incidence is of clear concern, patients with HPV-driven OPC generally have a better prognosis compared to those patients who are HPV-negative [14].…”
Section: Introductionmentioning
confidence: 99%
“…HPV-positive oropharyngeal cancers are more likely to occur in sexually active individuals, such as those who report oro-genital sex (Dahlstrom et al, 2015;Nguyen et al, 2016;Rettig, Kiess, & Fakhry, 2015;Schnelle, Whiteman, Porceddu, Panizza, & Antonsson, 2017) or even any sex (Chaturvedi, Graubard, Pickard, Xiao, & Gillison, 2014;Gillison et al, 2012), with more oro-genital sex partners increasing the risk of infection (Dahlstrom et al, 2015;Nguyen et al, 2016;Rettig et al, 2015;Schnelle et al, 2017). The major mechanism of transmission of HPV to the upper aerodigestive tract is considered to be with oral-genital contact (Dahlstrom et al, 2015;Schnelle et al, 2017). The Centers for Disease Control (CDC) recommends the use of barriers such as condoms and dental dams during orogenital sex to reduce the likelihood of getting or transmitting sexually transmitted infections (CDC, 2017b(CDC, , 2017c, and it has been suggested that using protection during oro-genital sex can reduce the risk of HPV transmission (Nguyen et al, 2016).…”
mentioning
confidence: 99%